Sound Absorption Coefficient of Coir Fibre with Poly-Lactic Acid (PLA) / Solehuddin Shuib ... [et al.] - Shuib, Solehuddin; Yahya, Muhd Azman; Abdullah, Abdul Hakim; Kamaruddin, Nur Syafiqah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This project involves the study of the sound absorption coefficient of a composite material made from coir fibre reinforced with poly lactic acid (PLA). Sound absorption coefficient, α is the value of sound that the material can absorb. This study was conducted to investigate the sound absorption properties of coir fibre composite based on the different values of coir fibre ratio. It also determined whether the coir fibre composite is suitable or not to be used as noise level reducer in the spaces like room or hall. The sound absorption coefficient's values of the test specimens for low and high-frequency bands were determined experimentally using the impedance tube method or known as two-microphone transfer function method with the range of frequency around 500-4500Hz by referring to the ISO 10534-2 standard procedure. The result of the sound absorption coefficient was processed using Audacity software and LDS Dactron Photon signal analyser while the results were presented in graph form using MATLAB. The characteristics of the sound absorption coefficient for each coir fibre ratio were discussed based on the range of frequency used. For the specimen with higher fibre ratio, it had a higher value of alpha, α compared to the lower fibre ratio. In conclusion, the specimen with the highest amount of fibre ratio has better sound absorption coefficient which the value is 0.98 compared to the specimen with lowest fibre content which is 0.3. Thus, higher fibre content is more suitable to be used as a noise level reducer.